Pengaruh Pengungkapan ESG (Environmental, Social Dan Governance) Terhadap Return Saham(Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI Periode 2020 – 2024) - Eva Putri Rahmadani; Tio Devilishanti (Indo Publishing, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on stock returns in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. ESG is a non-financial indicator that is increasingly being paid attention to by investors because it reflects the company's commitment to managing environmental, social, and governance risks, especially in the mining sector which has a high level of operational and reputational risk. This study uses a quantitative approach with secondary data obtained from annual reports and sustainability reports. The sampling technique used purposive sampling with a sample number of 15 companies, so that 75 research observations were obtained. The analysis method used is multiple linear regression with classical assumption test as a condition for model feasibility. The results of the study show that partially the Environmental variable has a positive but insignificant effect on stock returns, Social variables have a negative but insignificant effect on stock returns, while the Governance variable has a negative and significant effect on stock returns. Simultaneously, ESG disclosure has a significant effect on the return of shares of mining sector companies with a significance value of 0.019 < 0.05. The implications of this study show that ESG disclosure has an important role in influencing investor perception, so that mining sector companies are expected to improve the quality and consistency of ESG disclosure as part of a strategy to increase corporate value and investor confidence in the capital market.